Review: Granereau, A. (2020). O Livro de Lauzun: onde começou a Pedagogia da Alternância. Fortaleza: Edições UFC. - Alberto Dias Valadão (Universidade Federal do Norte do Tocantins, 2020)
The work of Abbé Granereau, Le livre de Lauzun - Une histoire des premières Maisons Familiales Rurales, published by Editora Gerbert à Áurillac, Paris, 1969, with a second edition by Editora L'Harmattan, Paris, 2007, is the result of the diary he produced consecutively describing the process of creating and expanding alternating training schools, the Maisons Familiales Rurales (MFR). The present work is a review of this work published in 2020 in Brazil by UFC Editions, which can be identified as the "Birth Certificate" of Pedagogy of Alternation. Granereau discusses how, philosophically and pedagogically, a new modality of political and educational nature was being structured in favor of farmers historically hitherto held hostage by a school that decanted urban values. The book portrays in detail the genesis of Pedagogy of Alternation, through the so-called Pedagogical Formula of Lauzun, focusing on: the difficulties of implementing new ideas that differ from ingrained pedagogical formulas; alternation of training between school and family-community time; didactic-pedagogical organization linking the two moments of study and work; and, the farmers taking over the management of the peasant school.